SPECIES COMPOSITION AND DISTRIBUTION OF BIVALVE (BIVALVIA) AND GASTROPODS (GASTROPODA) MOLLUSCA IN FRESHWATER RESERVOIRS OF DAGESTAN - Akhmed A. Abdulmedzhidov; Israp M. Israpov; Umagan A. Gapisova (Юг России: экология, развитие, 2017)
Aim. The aim of the study is to establish the taxonomic composition of freshwater mollusks and to study the patterns of their distribution over freshwater bodies located in different natural zones of Dagestan. Methods. The materials presented in this paper are predominantly collected in the summer months of 2000-2015 in the water bodies located in different natural zones of Dagestan: the Tersko-Sulak plain, the Primorsky lowland, the foothill area and the highland area. Results and conclusions. In the fresh waters of the investigated region, the class of bivalve mollusks is represented by 15 species from 10 genera and 5 families. The class of gastropods is represented by 34 species from 16 genera and 7 families. In the reservoirs and watercourses of the Tersko-Sulak plain zone, are found all 49 species of mollusks inhabiting the water bodies of the investigated area; 17 in the Primorsky lowland, 15 in the foothill area. Malacofauna of water bodies and streams of the highland areas is poor. Here were found only 6 species. The regions of distribution of mollusks that we have identified quite well correspond to the zoning of reservoirs according to their physical and geographical characteristics.